72-hour epidural infusion of 0.125% levobupivacaine following total knee replacement: a prospective, randomized, controlled, multicenter evaluation - Casati, A.; Ostroff, R.; Cassimoro, et al., C. (Acta Biomedica Atenei Parmensis, 2008)
Background and aim of the work: To evaluate the efficacy in terms of pain relief and degree of motor impairment of a continuous epidural infusion of 0.125% levobupivacaine in patients undergoing total knee replacement surgery. Methods: 186 patients receiving effective epidural analgesia with 0.125% levobupivacaine during the first 24 hours after surgery were randomly allocated to receive postoperative analgesia for the following 48 hours consisting in either a continued epidural infusion of 0.125% levobupivacaine (Levobupivacaine group, n = 96), or IV PCA morphine only (Morphine PCA group, n = 90). An independent observer recorded the average amount of morphine required per hour following randomisation, pain intensity, degree of motor blockade and occurrence of side effects. Results: Median (range) hourly morphine consumption during the study period was 0.21 (0.00-4.65) mg/hr in the Levobupivacaine group and 0.43 (0.04-4.65) mg/hr in the Morphine PCA group (P = 0.005). The quality of pain relief was adequate (VAS < 30 mm) in both groups, but patients in the Levobupivacaine group showed lower VAS values during motion than patients in the Morphine PCA group (P = 0.001). No differences in the proportion of patients with clinically relevant motor block (Bromage’s score 3 1) were reported between the two groups. Conclusions: Continuing the epidural infusion of a concentration of levobupivacaine as low as 0.125% improves pain relief with a 50% reduction of hourly morphine consumption after total knee replacement even during the second and third postoperative days, and does not result in a gross impairment of motor function.